The model of the formation of the management competence of future officers of fire safety in the process of their professional training - Король, В. М. (Pedagogy of Higher and Secondary Education, 2013)
Korol V. The model of the formation of the management competence of future officers of fire safety in the process of their professional training. Methodological and theoretical grounding of the model of the formation of the management competence of future officers of fire safety in the process of their professional training on the basis of the subjective, activity and competence approaches is dealt in the article. The author of the article reveals the sense of its every component.